Enhanced organic photovoltaic performance through promoting crystallinity of photoactive layer and conductivity of hole-transporting layer by V2O5 doped PEDOT:PSS hole-transporting layers. (15th November 2020) - Li, Jianfeng; Qin, Jicheng; Liu, Xingpeng; Ren, Meiling; Tong, Junfeng; Zheng, Nan; Chen, Weichao; Xia, Yangjun
Graphical abstract: Highlights: The V2 O5 nanoparticles can fill the pinholes in PEDOT:PSS. The hole transport layer of V2 O5 :PEDOT:PSS has high conductivity and hydrophobicity. The crystallizability of the active layer is improved by adjusting the interface. The PCE over 9.4% and FF over 70% can be achieved in OSCs with composite HTL. Abstract: The fill factor (FF) as an important photovoltaic parameter is related to the property of transport layers and active layers for organic solar cells (OSCs). Herein, we propose a simple method to improve FF by using inorganic-organic composite hole transport layer (HTL) in OSCs. Through incorporating inorganic metal oxide, vanadium pentoxide (V2 O5 ) nanoparticles into PEDOT:PSS, the morphology and conductivity of the composite HTL are improved, due to V2 O5 nanoparticles can fill the pinholes in PEDOT:PSS and expose more PEDOT chains to the surface core–shell structure. The PTB7-Th:PC71 BM-based OSCs with different HTLs were prepared. The power conversion efficiency and FF of the OSCs for the composite HTL can be greatly improved compared with the traditional HTL, which can reach up to 9.44% and 70.14%, respectively. The results of water contact angle and grazing incidence wide-angle X-ray scattering show that the hydrophobicity of the composite HTL is improved, which can not only improve the physical contact but also greatly affect the subsequent active layer formation, thus increasing the crystallinity of PTB7-Th:PC71 BM. These results demonstrate that V2 O5 :PEDOT:PSS has good application prospects as a HTL to realize high-efficient OSCs.